1978
DOI: 10.1212/wnl.28.11.1166
|View full text |Cite
|
Sign up to set email alerts
|

An extraordinary form of confabulation

Abstract: We describe five patients with spontaneous, persistent confabulation. While the basis of confabulation in general is not known, the evidence in this specific group of patients with spectacular, impulsive, and spontaneous confabulation suggests a marked deficit in frontal function, superimposed upon a basic defect in memory, as a possible mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Confabulation has frequently been characterised as an amnesia overlaid with a dysexecutive syndrome (Baddeley and Wilson, 1988;De Luca and Diamond, 1995;Kern et al, 1992;Kopelman, 1987;Kapur and Coughlan, 1980;Mercer et al, 1977;Shapiro et al, 1981;Stuss et al, 1978). If so, confabulation in these eight patients should be attributable to a combination of impairments in memory and executive functioning.…”
Section: Confabulation: a Combined Memory And Executive Function Defimentioning
confidence: 99%
See 2 more Smart Citations
“…Confabulation has frequently been characterised as an amnesia overlaid with a dysexecutive syndrome (Baddeley and Wilson, 1988;De Luca and Diamond, 1995;Kern et al, 1992;Kopelman, 1987;Kapur and Coughlan, 1980;Mercer et al, 1977;Shapiro et al, 1981;Stuss et al, 1978). If so, confabulation in these eight patients should be attributable to a combination of impairments in memory and executive functioning.…”
Section: Confabulation: a Combined Memory And Executive Function Defimentioning
confidence: 99%
“…Confabulation is frequently reported in association with aetiologies involving frontal lobe damage, including rupture and repair of anterior communicating artery aneurysms (Alexander and Freedman, 1984;Baddeley and Wilson, 1988;Burgess and McNeil, 1999;Dab et al, 1999;Damasio et al, 1985;DeLuca and Diamond, 1995;DelbecqDerouesne et al, 1990;Fischer et al, 1995;Kapur and Coughlan, 1980;Kopelman et al, 1995;Moscovitch 1989;Stuss et al, 1978;Vilkki, 1985), posterior communicating artery aneurysms (Dalla Barba et al, 1997;Mercer et al, 1977), frontal tumours (Fotopoulou et al, 2004), head injury (Baddeley and Wilson, 1988;Berlyne, 1972;Box et al, 1999;Damasio et al, 1985;Demery et al, 2001;Moscovitch and Melo, 1997), frontotemporal dementia (Nedjam et al, 2000; Moscovitch and Melo , 1 9 9 7 ) , K o r s a k o f f ' s s y n d r o m e (Berlyne, 1972;Benson et al, 1996;Dalla Barba et al, 1990;Kopelman, 1987;Kopelman et al, 1997;Korsakoff, 1955;Mercer et al, 1977;Talland, 1965), A l z h e i m e r ' s d i s e a s e ( D a l l a B a r b a et al, Kern et al, 1992;Kopelman, 1987;Nedjam et al, 2000;Tallberg and Almkvist, 2001), and herpes simplex encephalitis (Del Grosso Destreri et al, 2002;Moscovitch and Melo, 1997). Nearly all the evidence regarding the critical lesion site has come fro...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have obtained variable findings with respect to the association between executive test performance and confabulation, some reporting strong associations (e.g. (Stuss et al, 1978;Kapur & Coughlan, 1980;DeLuca & Cicerone, 1991;DeLuca & Locker, 1996;) and others reporting weak or no association (Gilboa, et al, 2006;Bouzerda-Wahlen et al, 2013). Johnson et al (1997) suggested that a weak autobiographical memory was also a factor promoting confabulation on the basis of a single case but, to our knowledge, this has not been systematically demonstrated before.…”
Section: Memory and Executive Function In The Onset Of Confabulationmentioning
confidence: 53%
“…Nevertheless, there appears to be considerable agreement that spontaneous confabulation arises when executive dysfunction and frontal lobe damage are superimposed upon an amnesic deficit (Luria, 1976;Stuss, Alexander, Lieberman, & Levine, 1978); Kapur & Coughlan, 1980;Baddeley & Wilson, 1986). Moreover, more recent neuroimaging and evoked potential investigations have particularly pinpointed damage within the ventro-medial and/or orbito-frontal brain regions (Schnider, 2003;Gilboa et al, 2006;Toosy et al, 2008;Turner, Cipolotti, Yousry, & Shallice, 2008;Gilboa & Verfaellie, 2010;Nahum, Bouzerda-Wahlen, Guggisberg, Ptak, & Schnider, 2012;Hebscher, Barkan-Abramski, Goldsmith, Aharon-Peretz, & Gilboa, 2015;Schnider et al, 2013;Manuel, David, Bikson, & Schnider, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%